The Effects of Adipose-Derived Mesenchymal Stem Cells and Adipose-Derived Mesenchymal Stem Cell-Originating Exosomes on Nerve Allograft Regeneration: An Experimental Study in Rats - Koplay, Tugba Gun; Yildiran, Gokce; Dursunoglu, Duygu; Aktan, Murad; Duman, Selcuk; Akdag, Osman; Karamese, Mehtap; Tosun, Zekeriya (Annals of plastic surgery, 2023)
Nerve regeneration has been the subject of many studies because of its complex mechanism and functional outcome. Mesenchymal stem cells and exosomes are promising factors in regeneration in many areas. Reconstruction of nerve defects is a controversial issue, and nerve allografts are promising alternatives with many advantages. In this study, it is aimed to evaluate the nerve regeneration in cellularized and decellularized nerve allografts and whether it is possible to accelerate this process with adipose-derived mesenchymal stem cells (ad MSC) or ad MSC-originating exosomes. This study was performed with 36 Lewis and 18 Brown Norway isogenic male rats aged 10 to 12 weeks and weighing 300 to 350 g. The Lewis rats were divided into 6 groups. Nerve allografts at a length of 12 mm that were obtained from the Brown Norway rats' proximal portion of both sciatic nerve branching points were coapted as cellularized in group A and decellularized in group B to the sciatic nerve defects of the Lewis rats. Group A received oral tacrolimus (0.2 mg/kg) for 30 days. Perineural saline (A1-B1), ad MSC (A2-B2), or ad MSC-originating exosomes (A3-B3) were applied to these groups. Walking track analysis, pinch-prick test and electromyelography were applied at the 8th and 16th weeks following surgery. Nerves were examined histopathologically at the 16th week. Between cellularized groups, better results were shown in A3 about axon-myelin regeneration/organization (P = 0.001), endoneural connective tissue (P = 0.005), and inflammation (P = 0.004). Better results were shown in the B2 and B3 groups electromyelographicaly about latency period (P = 0.033) and action potential (P = 0.008) at late period, and histomorphologicaly at vascularization (P = 0.012). It is argued that regeneration is accelerated with decellularization of nerve allografts by removing the chondroidin sulfate proteoglycans. The positive effects of stem cells are derived by exosomes without the cell-related disadvantages. In this study, better results were obtained by decellularization and perineural application of ad MSC and/or ad MSC exosome.